Spatial Hearing The Psychophysics of Human Sound Localization - Blauert, Jens (The MIT Press, 1996)
The field of spatial hearing has exploded in the decade or so since Jens Blauert's classic work on acoustics was first published in English. This revised edition adds a new chapter that describes developments in such areas as auditory virtual reality (an important field of application that is based mainly on the physics of spatial hearing), binaural technology (modeling speech enhancement by binaural hearing), and spatial sound-field mapping. The chapter also includes recent research on the precedence effect that provides clear experimental evidence that cognition plays a significant role in spatial hearing. The remaining four chapters in this comprehensive reference cover auditory research procedures and psychometric methods, spatial hearing with one sound source, spatial hearing with multiple sound sources and in enclosed spaces, and progress and trends from 1972 (the first German edition) to 1983 (the first English edition)-work that includes research on the physics of the external ear, and the application of signal processing theory to modeling the spatial hearing process. There is an extensive bibliography of more than 900 items.